CLIMA ORGANIZACIONAL E BURNOUT: UM ESTUDO COM SERVIDORES PÚBLICOS FEDERAIS - Infante, Lucyene Pereira Pinto (2016)
The unsuitable conditions lived by corporations is affecting not only workers from private companies, but are also equally found in the state-based corporations, counteracting the expectations that the government apparatus would eliminate the unhealthy conditions and could created better ones, prevailing the health promotion. Facing this scenario, it is still to be known why it is a common sense in our society that workers hired by the government are submitted to better work conditions and health insurance when compared to private companies’ workers. This study aims to identify and describe the possible relations between the organizational environment and the Burnout in government employees from a federal educational institution.It will also describe the present and dominant organizational environment. The current study has a quantitative nature as well as a deep and exploratory study case. The data presented was obtained by the use of the organizational climate scale (ECO), the Burnout Characterization Scale (ECB) and a sociodemographic questionnaire. All the electronic automatically self- applicable instruments were available for the institution. 201 public agents participated in the study, the average age was 37, predominantly graduated and married. The results revealed that one quarter of the participants rarely experimented burnout; however another quarter is frequently experimenting burnout. The workers noticed an average organization climate, highlighting a good cohesion among the fellow workers coworkers and concluded that the reward is low. Another highlight is the big dispersion between the climate perceptions, which leads to the conclusion that there are still unidentified subclimates in the current investigation, possibly occasioned by a weak force of climate and by the participation of employees from different teaching units, administrated by local managers with relative autonomy. The result of the calculations of correlation revealed that, the less support given by the managers and the institution, cohesion between coworkers and more control/pressure received, more exhausted they feel which leads to a worse relation between the people in contact with the workers and the disappointment at work grows. Physical comfort is less associated with this issue, and control/pressure is both positively and negatively associated with the contact between the workers and the people. Therefore, the hypothesis that there is a link between burnout and organizational climate was confirmed. The results also revealed that workers with burnout noticed a worse climate than workers without burnout, confirming the second hypothesis. These workers also revealed themselves neutral when questioned about support from superiors and physical comfort, do not notice control/pressure, neither reward, however they do realize the cohesion between the coworkers. The result suggests that the workers use this relation to tolerate the indifference and lack of stimulation experienced at work. The results obtained by this study concluded that the organizational climate is weak, and probably influenced by an insufficient organizational culture, explaining the heterogeneity of the perception of the climate lived by the workers. Although there is burnout between a few participants, it should be noted that one quarter of them is currently stricken in this syndrome and it potentially could affect the others.